Delayed auditory feedback increases speech production variability in typically fluent adults but has the opposite effect in stuttering adults - Daliri, Ayoub; Honda, Shogo; Max, Ludo (Frontiers in Human Neuroscience, 2025)
PurposeExtensive evidence indicates that auditory-motor integration during speech production is inefficient in individuals who stutter and that speaking with delayed auditory feedback (DAF) increases speech fluency in this population. However, the exact mechanisms underlying these auditory-motor integration difficulties and the DAF-induced fluency enhancement remain unknown. Here, we examined (1) whether stuttering is associated with increased variability in the feedforward component of sensorimotor control and (2) whether speaking with DAF reduces this variability in speech movement planning in adults who stutter.MethodWe extracted acoustic measures from audio recordings made during a prior study that included 12 right-handed adults who stutter and 12 age-, sex-, and handedness-matched nonstuttering adults. Participants produced front vowels in the context of monosyllabic consonant-vowel-consonant words in conditions where they spoke with either normal auditory feedback (NAF) or 100-ms DAF. For each participant in each condition, we calculated trial-to-trial formant variability to assess feedforward processes.ResultsRelative to nonstuttering adults, stuttering adults generally showed greater trial-to-trial formant variability. DAF had a differential influence on trial-to-trial formant variability, increasing it for non-stuttering adults but decreasing it for stuttering adults.ConclusionThese findings suggest that stuttering adults generated more variable motor commands than nonstuttering adults when speaking with NAF, but that speaking with DAF decreased variability in the stuttering group, even though it increased variability in the nonstuttering group. One possible interpretation of these findings is that stuttering modulates the sensorimotor system’s processing of auditory errors, specifically influencing how significantly these errors are weighted when the sensorimotor system determines its responses to the errors.